Transformation of Science Learning in Madrasah Ibtidaiyah Post-Pandemic: A Case Study of Teacher and Student Adaptation to Blended Learning at Madrasah Ibtidaiyah Nurul Ulum Mertak Tombok - Mukminah, Mukminah; Ningsih, Dewi Puspita; Hirlan, Hirlan (Sean Institute, 2025)
The Covid-19 pandemic has marked a turning point in the transformation of educational systems, including at the level of primary Islamic schools (madrasah ibtidaiyah), which are now required to adapt to more flexible learning models. Blended Learning, as a combination of face-to-face and online instruction, has emerged as a strategic approach in the post-pandemic context to address the challenges of sustainable learning. This study aims to explore the adaptation processes of teachers and students to the implementation of Blended Learning in science education at Madrasah Ibtidaiyah Nurul Ulum Mertak Tombok, Central Lombok Regency. Employing a qualitative approach through a case study method, data were collected via observations, interviews, and documentation. The findings indicate that teachers have experienced a paradigm shift in designing learning strategies that are more adaptive and responsive to students' needs. Meanwhile, students face challenges in managing their study time, limited access to technology, and fluctuating motivation to learn. Nevertheless, the majority of students reported that blended learning provides a more varied and enjoyable learning experience. These findings reinforce previous studies that emphasise the importance of infrastructure readiness and the active role of teachers in supporting the effectiveness of learning. The implications of this research underscore the necessity of enhancing teachers' digital competencies and the support of school policies in the sustainable and contextual implementation of Blended Learning.